Research on parallel partheno genetic algorithm based on the immune programming - XING Xiao-shuai; HUO Bing-peng (Tongxin xuebao)
A novel algorithm parallel partheno genetic algorithm based on the immune programming（IPPPGA） was proposed,the algorithm analogies to the concept and theory of immunity in biotic science and unifies the parallel compu-tation thought,after analyzing the advantages and disadvantages of the partheno genetic algorithm.The theory analysis and experimental results show that the algorithm not only effectively keeps population diversity,but also alleviates the undulate phenomenon in evolutionary latter stages,meanwhile increases the convergent speed and computational effi-ciency greatly.